THE CORRELATION BETWEEN THE MEAN PLATELET VOLUME VALUES WITH THROMBOCYTE AGGREGATION IN NEPHROPATHY DIABETIC PATIENTS - Agus Sunardi; Nadjwa Zamalek Dalimoenthe; Coriejati Rita; Adhi Kristianto Sugianli (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Diabetic nephropathy is the most important cause of end-stage renal failure. Chronic hyperglycemia will cause glomerular endothelial damage, and this damage will stimulate hemostasis activation including platelets so that platelet aggregation will increase. The increase of platelet aggregation will increase platelet consumption, which further stimulates thrombopoiesis which will lead to immature platelets of large size to be released into the circulation. This research aimed to determine the positive correlation between MPV with platelet aggregation in patients with diabetic nephropathy. This study was an analytic observational study with a cross-sectional study design. The research was conducted in the Dr. Hasan Sadikin Hospital Bandung from July 2016 to October 2017. A total of 52 subjects who met the inclusion criteria were included in the study. Mean platelet volume and platelet aggregation were performed with venous examination with EDTA and sodium citrate 3.2% anticoagulants. The result of platelet aggregation examination showing platelet hyper-aggregation was found in 44.2% of subjects, 50% normal-aggregation, 5.8% hypo-aggregation. While the median value of MPV in this study was 9.2 fL with the range of 8.00 – 11.80 fL. A positive correlation was found between MPV value with platelet aggregation with r= 0.067, p= 0.634. The conclusion was that there was no correlation between MPV values with platelet aggregation in diabetic nephropathy patients. This small and insignificant r-value might be due to several factors that also affect platelet aggregation in diabetic nephropathy patients, requiring further investigation.